Physics‐Based Hazard Assessment of Compound Flooding From Tropical and Extratropical Cyclones in a Warming Climate - Ali Sarhadi; Raphaël Rousseau‐Rizzi; Kerry Emanuel (Earth's Future)
Abstract Recent efforts to assess coastal compound surge and rainfall‐driven flooding hazard from tropical (TCs) and extratropical cyclones (ETCs) in a warming climate have intensified. However, challenges persist in gaining actionable insights into the changing magnitude and spatial variability of these hazards. We employ a physics‐based hydrodynamic framework to numerically simulate compound flooding from TCs and ETCs in both current and future climates, focusing on the western side of Buzzards Bay in Massachusetts. Our approach leverages hydrodynamic models driven by extensive sets of synthetic TCs downscaled from CMIP6 climate models. We also perform a far less extensive analysis of ETCs using a previously produced event set, dynamically downscaled using the WRF model driven by a single CMIP5 model. This methodology quantifies how climate change may reshape the compound flooding hazard landscape in the study area. Our findings reveal a significant increase in TC‐induced compound flooding hazard due to evolving climatology and sea level rise (SLR). Although compound flooding induced by ETCs increases mostly in coastal areas due to SLR, inland areas exhibit almost no change, and some even show a decline in rainfall‐driven flooding from high‐frequency ETC events toward the end of the century compared to the current climate. Our methodology is transferable to vulnerable coastal regions, serving as a tool for adaptive measures in populated areas. It equips decision‐makers and stakeholders with the means to mitigate the destructive impacts of compound flooding arising from both current and future TCs, and shows how the same methodology might be applied to ETCs.